Sanitary and Hygienic Assessment of the Arrangement of «Clean Rooms» in the Projects of Surgical, Obstetric Hospitals and Pharmaceutical Companies - Manenko, Алек; Kasyian, Ольга; Tkachenko, Галина; Danylyshyn, Надія; Holovatska, Жанна (Actual Problems of Medicine and Pharmacy, 2022)
The designers and the administration of health care institutions face the urgent need to adapt the regulatory and technological documentation of Ukraine to the requirements of ISO 14644-1:1999 IDT «Clean rooms and related controlled environments. Part 1. Classification of cleanliness «for the construction of» clean rooms «in the reconstruction projects of surgical and obstetric hospitals, and modern pharmaceutical companies cannot produce competitive products without the introduction of» clean rooms «in the process of ISO, GMP, GLP - the best production and laboratory practices.